Analysis of patients with systemic diseases and their prevalence of periodontal disease in the clinic of the Specialty of Periodontics at the School of Dentistry of the Universidad Abierta Interamericana - Forciniti , Estefanía (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Periodontal diseases, especially periodontitis, were associated with systemic and social factors. Recent studies showed their relationship with cardiovascular diseases, diabetes, osteoporosis and smoking, with diabetes being a significant factor that aggravated the progression and severity of periodontitis. The prevalence of severe periodontitis increased between 30 and 40 years of age and remained stable at older ages. Factors such as socioeconomic level, habits such as smoking and poor oral hygiene, and systemic conditions, such as hypertension and diabetes, played a determining role in the progression of this pathology.Smoking represented a critical risk, associated with greater severity and incidence of periodontitis. Abandoning this habit significantly reduced the risk. Likewise, people with diabetes had a 2.6 to 3 times higher risk of developing periodontitis, with a more aggressive progression. The studies also suggested a relationship between periodontal disease and hypertension, although further research was needed to establish causality.The data analyzed revealed that prevalence varied with age, habits and systemic conditions. Although factors such as lifestyle and socioeconomic status were not directly associated with systemic pathologies, they significantly influenced periodontal health. It was concluded that these patients required personalized treatment and follow-up to prevent complications. It was essential to standardize evaluation and diagnostic methods to improve the understanding and management of this disease